2013
DOI: 10.7567/jjap.52.07hd08
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Energy Harvesters Integrated with a Quatrefoil-Shaped Proof Mass Suspended by Multiple (K,Na)NbO3Beams

Abstract: In this study, we developed an energy harvester with a multibeam structure employing a (K,Na)NbO3 (KNN) thin film. The harvester had a quatrefoil-shaped proof mass suspended by four KNN beams and was completely fabricated by micromachining technologies. The harvester was designed to obtain high nonlinearity. As a result, the fractional bandwidth of operable frequency was widened by more than 40% when the acceleration was 15 m/s2. The maximum harvested power of 640 nW was obtained at the resonant frequency of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…[15][16][17][18][19][20][21] We have also demonstrated that MEMS cantilever-type energy harvesters using (100)-oriented BiFeO 3 films show the normalized output power of 0.9 µW•G −2 •mm −2 , which exceeds or is comparable to the best-performing piezoelectric energy harvesters using other piezoelectric films, such as PZT, (K,Na)NbO 3 (KNN), and AlN. 19,[22][23][24][25] We have also observed the hard spring effect due to the nonlinearity of the cantilever vibration in the measurement results under sinusoidal vibration. When the vibrational frequency ramps up and down around a resonant frequency, the hysteresis is observed in the frequency dependence of output voltage.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…[15][16][17][18][19][20][21] We have also demonstrated that MEMS cantilever-type energy harvesters using (100)-oriented BiFeO 3 films show the normalized output power of 0.9 µW•G −2 •mm −2 , which exceeds or is comparable to the best-performing piezoelectric energy harvesters using other piezoelectric films, such as PZT, (K,Na)NbO 3 (KNN), and AlN. 19,[22][23][24][25] We have also observed the hard spring effect due to the nonlinearity of the cantilever vibration in the measurement results under sinusoidal vibration. When the vibrational frequency ramps up and down around a resonant frequency, the hysteresis is observed in the frequency dependence of output voltage.…”
Section: Introductionmentioning
confidence: 84%
“…The bandwidth of the piezoelectric MEMS cantilever-type vibrational energy harvesters could be increased by the soft or hard spring effect. 25) In general, increasing the bandwidth is important for generating the output power efficiently since the environmental vibration is distributed in the broad frequency domain. The power generation under random vibration is proportional to the square of the acceleration also in the nonlinear region.…”
Section: Power (Nw)mentioning
confidence: 99%
See 1 more Smart Citation
“…Excitingly, the piezoelectric energy harvester (PEH) is a device that can convert waste mechanical energy in the environment into usable electrical energy and has shown the ability to replace batteries and enable self-powered wireless sensors. [2][3][4][5][6] The figure of merit (FOM), expressed as FOM = d 2 /e (d is the piezoelectric charge coefficient, and e is the dielectric permittivity), is an important material parameter that directly determines whether PEHs have high power density. 7 Besides, PEHs mainly work in vibrational environments to realize electromechanical conversion, which requires piezoceramics with excellent fracture toughness to ensure long-term stable operation without failure.…”
Section: Introductionmentioning
confidence: 99%
“…To meet these requirements, various types of energy harvester have been reported today. 8,9) Among them, a cantilever-based piezoelectric energy harvester (CPEH) can provide an excellent solution. In the CPEH, a large deformation can be induced in the piezoelectric film exploiting the lever structure with a larde proof mass.…”
Section: Introductionmentioning
confidence: 99%